Implementasi Algoritma K-Modes Untuk Mengukur Tingkat Kepuasan Mahasiswa Terhadap Pembelajaran Daring - Desyanti, Desyanti; Yusrizal, Yusrizal; Sari, Febrina (Forum Kerjasama Pendidikan Tinggi, 2022)
The outbreak of the corona virus outbreak has made the economic system, education system and other systems very chaotic. That is why Dumai College of Technology has participated in implementing online learning from March 2020 to June 2021 in accordance with government regulations. Brave learning is an alternative in overcoming the lecture system, so students no longer come to campus and only attend lectures from home. Although learning activities are carried out boldly, lectures must still pay attention to the quality and quality of learning, that's why we need a method to analyze the level of student satisfaction in the bold learning process, which can later be used as evaluation material by the campus. The use of the k-modes clustering algorithm is to group the satisfaction results into several clusters including very satisfied, satisfied, dissatisfied and very dissatisfied and the data processed is data in the form of categorical data or data in the form of classification by performing matching equations between training data and centroids for looking for the closest distance and the value of the objective equation, the sample used was 100 respondents who filled out the satisfaction assessment questionnaire, from the results of the questionnaire data processing the cluster was very satisfied with a percentage of 22%, the cluster was satisfied 69%, the cluster was not satisfied 5% and the last in the very dissatisfied cluster as much as 4%